Two new species of Bairdiidae (Ostracoda: Crustacea) from the western Pacific coast of Japan - Horikoshi, Hideyuki; Nakao, Yuriko; Tsukagoshi, Akira (Zootaxa, 2019)
Herein, two new bairdiid ostracod species in the western Pacific Coast of Japan, namely Neonesidea kamiyai sp. nov. and Bairdoppilata japonica sp. nov. are described. They are the fourth and first species described in their respective genus in Japan within the Recent Bairdiidae. The description of the two new species is based on scanning electron microscopic investigation of carapaces and on the analysis of anatomy and chaetotaxy of appendages. Scanning electron microscopy of the carapace and soft-part anatomy of appendages of the two new species provided the complete species description. An asymmetric brush-shaped organ, with the right part considerably larger than the left part, is found in both species; this characteristic is suggested to be synapomorphic for some taxa in the family Bairdiidae.